2020
DOI: 10.2147/ott.s243215
|View full text |Cite
|
Sign up to set email alerts
|

<p>Loss of miR-204-5p Promotes Tumor Proliferation, Migration, and Invasion Through Targeting YWHAZ/PI3K/AKT Pathway in Esophageal Squamous Cell Carcinoma</p>

Abstract: MicroRNAs dysregulation has been confirmed in multiple malignancies. This paper reported the molecular mechanism of miR-204-5p in esophageal squamous cell carcinoma (ESCC). Methods: miR-204-5p expression in 30 ESCC tumor tissues and 10 normal tissues was downloaded from RNA-seq data. ESCC tissues/normal tissues of 97 ESCC patients were collected. TE-1 and KYSE510 cells were transfected by miR-204-5p mimic, inhibitor, siYWHAZ or their corresponding controls. The phenotype of cells was detected by CCK-8 assay, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Similarly, research studies have shown that miR-204-5p in cells and patients with esophageal squamous cell carcinoma is lower than that in normal tissues and cells, and it has also shown that the continuous decline of miR-204-5p is bound up with unfavorable prognosis of sufferers [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research studies have shown that miR-204-5p in cells and patients with esophageal squamous cell carcinoma is lower than that in normal tissues and cells, and it has also shown that the continuous decline of miR-204-5p is bound up with unfavorable prognosis of sufferers [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported the interaction between AKT and HIFcould exert great effects on the progression of NSCLC [20]. Interestingly, miR-204-5p expression was reduced in esophageal squamous cell carcinoma, and miR-204-5p repressed the development of esophageal squamous cell carcinoma by blocking the PI3K/AKT pathway [21]. Thus, we reasoned that MSCs-derived exosomes containing miR-204 could restrain NSCLC cell malignant phenotype via the KLF7/HIF-axis.…”
mentioning
confidence: 95%
“…In addition, previous studies have indicated that miR-204 suppresses cell proliferation, apoptosis, invasion and epithelial-mesenchymal transition (EMT) in ESCC [25][26][27]. Based on these studies, miR-204-5p was selected for this study.…”
Section: Identification Of Nestin-related Mirnasmentioning
confidence: 99%